2019
DOI: 10.48550/arxiv.1901.01624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composite optimization for robust blind deconvolution

Abstract: The blind deconvolution problem seeks to recover a pair of vectors from a set of rank one bilinear measurements. We consider a natural nonsmooth formulation of the problem and show that under standard statistical assumptions, its moduli of weak convexity, sharpness, and Lipschitz continuity are all dimension independent. This phenomenon persists even when up to half of the measurements are corrupted by noise. Consequently, standard algorithms, such as the subgradient and prox-linear methods, converge at a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…[24,Lemma 4.2]. In particular, a variety of practical problems in statistical signal recovery are weakly convex; see [14,15,19,34] for examples. for some closed function f : R d → R that is bounded from below on a closed set X ⊆ R d .…”
Section: Preliminariesmentioning
confidence: 99%
“…[24,Lemma 4.2]. In particular, a variety of practical problems in statistical signal recovery are weakly convex; see [14,15,19,34] for examples. for some closed function f : R d → R that is bounded from below on a closed set X ⊆ R d .…”
Section: Preliminariesmentioning
confidence: 99%
“…An increasing amount of research has shown how matrix recovery problems, which in the worst case are hard, become tractable under appropriate statistical assumptions. Examples include phase retrieval [2][3][4], blind deconvolution [1,5], matrix sensing [6,7], matrix completion [8,9], and robust PCA [10,11], among others [12][13][14][15]. Convex relaxations have proven to be a great tool to tackle these problems, but they often require lifting the problem to a higher dimensional space and consequently end up being computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…To tackle the blind deconvolution problem, [1] proposed the following nonconvex nonsmooth formulation argmin w,x f S (w, x)…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations